Designing Educational Contents in and for the Electronic Environment - Kišiček, Sanja; Boras, Damir; Bago, Petra (2010)
This paper is a preliminary report on the results of student projects developed within the elective course Computer Assisted Teaching in the Academic Year 2008-2009. The project goal was to create a purposeful opportunity for the students to directly participate in the educational system. By the help of information technology, the students developed educational materials in form of tutorials for usage in electronic educational environment. The tutorials’ subject matter is various and it is presented in English and in the Croatian Language including all segments of multimedia: text, graphics, animation, sound, video and computer test. The tutorials are formed as standalone lectures independent of a lecturer's physical presence. They are applicable in distance learning and computer assisted teaching for all levels of education.
Projekt MZOS
ENG